The Cypriot Presidential Election of 2023 and its Aftermath - Triga, Vasiliki; Ioannidis, Nikandros (My University, 2023)
The report presents a comprehensive analysis of the 2023 Cypriot presidential election, providing significant insights into the country's political system and social landscape. It explores critical themes of the election campaign, such as corruption, inflation, immigration, and the Cyprus problem, and assesses the potential implications of the election outcome.
Keywords: Cyprus; Presidential Elections